Nilai Berita Prominence Pada Program Wajar Sumut Di Metro TV Biro Sumbagut (Studi Analisis Wacana Kritis Tentang Teks Berita "Evaluasi Kinerja Walikota") - Yosefa Gunarty Tarigan; Rehia K. Isabella Barus; Taufik Wal Hidayat (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
This study aims to find out the analysis of Prominence news value discourse at the text level in the "Mayor Performance Evaluation" news. This study uses qualitative research with descriptive analysis. In collecting data, researchers conducted face-to-face interviews with Metro TV Bureau of the North Sumatra Bureau of Information. This type of research is text research. In the method, the researcher uses the Norman Fairclough Critical Discourse Analysis research method on the dimensions of text, on the elements of Representation, Relationships, and Identity, this model was chosen because Fairclough focuses the discourse on language, so that it is more focused on seeing how Metro TV Bureau of Sumbagut in reporting Performance Evaluations Mayor. The results showed that there were three elements in analyzing the text of the Mayor's Performance Evaluation based on Norman Fairclough's theory, namely Representation of the performance evaluation of the mayor, by reflecting the performance of the mayor who had not experienced changes or were realized; the relationship between journalists and news sources is very influential on the development of the mayor's performance; and Identity to see how journalists place themselves in the text and in this news, journalists position themselves as being in favor of the public.